The World of "Gigi" Game - Desy Nur Fitriana; Brenda Chandrawati (SISFORMA, 2016)
The continuously increasing oral and dental problems in Indonesia as well as the lack of cultivation of education provided is a problem that occurs. Planting early in children is an appropriate solution as a step to maintaining healthy teeth and mouth. Kids can further explore the game by playing while learning so that education as outlined in the game will be quickly absorbed by the child. Through the game The World Of Gigi became one medium of learning for children who are not at school or dentist about maintaining healthy teeth and mouth. The positive impact after playing the game The World Of Gigito 40 respondents obtained sebayak 97.5% or 39 respondents stated that after playing the game The World Of Gigi can know or understand about education around the teeth and mouth. And the whole of the respondents agreed that the game becomes interesting learning methods.